menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Given: 33 + 6p = 2(p-1) - 3p Prove: p = -5
asked
Mar 11, 2022
122k
views
7
votes
Given: 33 + 6p = 2(p-1) - 3p
Prove: p = -5
Mathematics
college
Norse
asked
by
Norse
4.8k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
2
Answers
11
votes
33 + 6 x -5 = 2(-5 - 1) - 3 x -5
3 = 3
Meet Taraviya
answered
Mar 12, 2022
by
Meet Taraviya
5.3k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
1
vote
Answer:
Let us prove that p=-5
33+ 6p= 2p-2-3p
33+6p= -1p-2
33+7p=-2
7p=-35
p=-5
Zack Lee
answered
Mar 18, 2022
by
Zack Lee
5.3k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.7m
questions
7.4m
answers
Other Questions
Evaluate a + b when a = –16.2 and b = –11.4 A. –27.6 B. –4.8 C. 4.8 D. 27.6
What is the value of x? (-4) - x = 5
Can someone help me with 5??? ASAP?
Solve for h 3h=7(2/7-3/7h)-10
1/7 + 3/14 equivalent fractions
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org